Analytical method development for polar pesticides using liquid chromatography - Devitte, Yury (2024)
The aim of this master’s thesis was to develop analysis methods for three commonly used and known pesticides, namely glyphosate, glufosinate and aminomethylphosphonic acid (AMPA). Two chromatography techniques were mainly used for these analysis procedures - hydrophilic interaction liquid chromatography with ultra-high performance liquid chromatography and tandem mass spectrometry (HILIC-UHPLC-MS/MS) and high-performance liquid with ultraviolet detection (HPLC-UV).